On the injectivity of the generalized Radon transform arising in a model of mathematical economics. (24th October 2016) - Agaltsov, A D
Abstract: In the present article we consider the uniqueness problem for the generalized Radon transform arising in a mathematical model of production. We prove uniqueness theorems for this transform and for the profit function in the corresponding model of production. Our approach is based on the multidimensional Wiener's approximation theorems.